From Boredom to Brilliance: Using TGT and Physics Ludo to Teach Newton’s Laws - Romadhon, Dzikri Rahmat; Faturrahman, Ahmad Riski; Farizi, Taufiq Al (Universitas Muhammadiyah Makassar, 2024)
This study investigated the effectiveness of the cooperative learning model Teams Games Tournament (TGT) assisted by Physics Ludo media in enhancing students' understanding of Newton's laws of gravity. Conducted at SMA Negeri 14 Bekasi City, the research involved an experimental group (grade 10 Science 1) using the TGT model and a control group (grade 10 Science 3) following conventional teaching methods. Pretest and posttest scores were analyzed using the Wilcoxon Signed-Rank test, independent samples t-test, and Mann-Whitney U test to determine the impact of the intervention. The results revealed that both the experimental group (Wilcoxon Signed-Rank test, p = 5.82×10⁻¹¹) and the control group (p = 5.26×10⁻⁸) showed significant improvements in posttest scores compared to their pretest scores. Additionally, an Independent Samples t-Test indicated that the experimental group scored significantly higher than the control group in the posttest (t = 10.80, p = 2.16×10⁻¹⁶). The Mann-Whitney U Test further demonstrated that the experimental group had greater improvement scores than the control group (U = 1225.0, p = 4.79×10⁻¹³). These statistical findings confirm the effectiveness of the TGT model with Physics Ludo. Moreover, survey feedback showed high levels of student engagement and motivation, with the majority finding the learning approach engaging and beneficial for understanding physics concepts. These findings highlighted the potential of game-based cooperative learning models to transform traditional educational practices, suggesting that further research and broader application could lead to enhanced learning outcomes in various subjects.